Answers

2015-05-06T20:13:45+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Formula is last term =first term -(n-1)difference
4=a+(2)d                                       equation 1
-8=a+8d                                        equation 2
 by solving both we get d=-2
then by substituting that in any of the equation we get the first term as 8
therefore the term which is 0 is 5th term   
0
off answer
this is wrong answer naa
this is correct but......
but not enough details so please elaborate it with the calculations
The Brainliest Answer!
2015-05-06T20:26:20+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
given 3rd term = 4
i.e, a+2d=4 ---- 1
and 9th term = -8
i.e., a+8d=-8 ------------- 2
by by subtacting 1 and 2 we get,
      a+2d = 4
      a+8d = -8
     -    -      +
     ----------------
        -6d = 12
     ---------------
so, d = -12/6
      d = -2
substitute it in (1) we get, 
a+2(-2) = 4
a = 4+4 =8
a=8

here we get a=8

2nd term = a+d = 8+(-2) = 8-2 = 6
3d term = a+2d = 8+2(-2) = 8-4 = 4
4th term = a+3d = 8+2(-3) = 8-6 = 2
5th term = a+4d = 8+2(-4) = 8-8 =0
6th term = a+5d =8+5(-2) = 8-10 = -2 .......

so the series we got is 8,6,4,2,0,-2.....
here we get zero at 5th place
so, 5th number in the series is 0

1 5 1
;)
pooja its ur bro
yaa i knw dear... my thammuduuu... thanks for choosing it as best
plz answer to my other que also
ok i will see it